2016
DOI: 10.21037/jtd.2016.12.89
|View full text |Cite
|
Sign up to set email alerts
|

Duration of antibiotic therapy in the intensive care unit

Abstract: There are certain well defined clinical situations where prolonged therapy is beneficial, but prolonged duration of antibiotic therapy is associated with increased resistance, medicalising effects, high costs and adverse drug reactions. The best way to decrease antibiotic duration is both to stop antibiotics when not needed (sterile invasive cultures with clinical improvement), not to start antibiotics when not indicated (treating colonization) and keep the antibiotic course as short as possible. The optimal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 33 publications
0
38
0
1
Order By: Relevance
“…In general, the studies conducted by Durgad AG et al, and Zilahi G et al, reported mean duration of 10 days of antibiotic therapy. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…In general, the studies conducted by Durgad AG et al, and Zilahi G et al, reported mean duration of 10 days of antibiotic therapy. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many patients are treated for longer courses when they have a highly resistant infection primarily out of an inherent concern for relapse, recrudescence, or treatment failure. 101,137 Adjunctive Therapy…”
Section: Duration Of Therapymentioning
confidence: 99%
“…otics as well as their administration when it is not necessary due to the increasing incidence of antibiotic-resistant pathogens (28,29).…”
Section: Figmentioning
confidence: 99%